Assessment of biventricular function using advanced echocardiography in patients with Ebstein's anomaly pre and post-tricuspid valve surgery. (25th November 2020) - Ricci, P; Ostenfeld, E; Flick, C; West, C; Babu-Narayan, S; Nihoyannopoulos, P; Li, W
Abstract: Background: Ebstein's anomaly (EA) is a right ventricular myopathy with failure of tricuspid valve (TV) delamination. While conventional echocardiographic measurements of ventricular function such as tricuspid annular plane systolic excursion (TAPSE), tissue Doppler imaging RV systolic velocity (s'), fractional area change (FAC) and left ventricle ejection fraction (LV EF) are load dependent measures of systolic function and may not reflect true myocardial function, speckle tracking echocardiography (STE) evaluates more subtle myocardial deformation on a regional level. However, the role of STE for the biventricular assessments in an adult cohort of EA before and after tricuspid valve repair/replacement (TVR) is not fully elucidated. Purposes: To assess biventricular function by conventional echocardiographic parameters and global and regional longitudinal strain (GLS, RLS) using speckle tracking echocardiography in adult patients with EA pre- and post-TVR. Methods: 47 patients with EA (57% women, age at operation 37±16 years) who had TV repair/replacement (17/30) between 2005 and 2019 were retrospectively identified from Echo database. 2D conventional echocardiographic parameters (TAPSE, s', FAC and LV EF) and biventricular GLS and RLS were assessed pre-TVR, at 1-, 2- and 5-year post-TVR. RV and LV segments were visually graded for STE feasibility assessment (Figure 1). Results: TAPSE and s' declined after TVR with no further changes over 5 years (both p<0.0001); FAC decreased after TVR (p=0.005) with some amelioration but remaining impaired at 5 years. RV GLS deteriorated at 1 year post-TVR with improvements at 2 and 5 years (p<0.0001, Table 1). LV EF remained preserved (p=0.2), however, LV GLS was low pre-TVR and decreased at 1 year with improvements at 2 and 5 years (p=0.004). Least feasible segments were RV mid (pre-TVR and 1y and 5y post-TVR) and apical free wall (both pre- and post-operative) and LV apical lateral (pre-TVR and 2y post-TVR) all with median score of 1. Conclusions: Despite the TV regurgitation reduction, TV surgeries have led to RV dysfunction with only some amelioration of RV longitudinal strain and all conventional echocardiographic parameters after 5 years. The segmental analysis showed that the basal septal segment was the most negatively affected. LV strain was reduced before and after surgery despite preserved ejection fraction. Hence, speckle tracking echocardiography is a feasible and a sensitive method in detecting myocardial dysfunction in patients with Ebstein's anomaly. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Royal Brompton Hospital; Imperial College